A Case of Prenatally Diagnosed Uhl’s Anomaly with Absent Pulmonary Valve Leaflets and Dysplastic Tricuspid Valve - Taehong Kim; Hoon Ko; Joung-Hee Byun; Hyoung Doo Lee; Hyungtae Kim; Kwangho Choi; Joo-Young Na (Children, 2021)
Uhl’s anomaly is a very rare malformation of unknown cause, characterized by complete or partial absence of the right ventricular myocardium. The cardiac malformation causes progressive right heart failure, increased right-sided cardiac pressure, massive peripheral edema, and ascites. Patients usually present in infancy and rarely survive to adulthood. Previously, diagnosis was made at post-mortem evaluation, but advances in cardiac imaging now permit diagnosis during fetal life. We report a case of Uhl’s anomaly in a newborn baby imaged at 23 + 3 weeks of gestation by fetal echocardiography. There was an aneurysmally dilated thin-walled right ventricle with hypertrophy of the right ventricular apical muscles, the tricuspid valve was dysplastic, and the pulmonary valve leaflets were absent.